If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(10x + -2) = -4(-7 + 11) Reorder the terms: 3(-2 + 10x) = -4(-7 + 11) (-2 * 3 + 10x * 3) = -4(-7 + 11) (-6 + 30x) = -4(-7 + 11) Combine like terms: -7 + 11 = 4 -6 + 30x = -4(4) Multiply -4 * 4 -6 + 30x = -16 Solving -6 + 30x = -16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 30x = -16 + 6 Combine like terms: -6 + 6 = 0 0 + 30x = -16 + 6 30x = -16 + 6 Combine like terms: -16 + 6 = -10 30x = -10 Divide each side by '30'. x = -0.3333333333 Simplifying x = -0.3333333333
| 5x+12=4-3t | | -3+4x-4x=-26+2x | | x+2(-2)=8 | | 12+2x=4-x | | 3(t-2)=9(t-2) | | 5(x-5)=(14-4) | | 20x+5x-10=90 | | 4-w=3w | | 2r+1=5-11 | | .96y-0.79=0.21y+0.46 | | 6x^2-x+1=3 | | 3x-2x=14+3x | | 6.8y-2.4y=88 | | 2x=5x-2 | | 0.5x+6=x^2+12x | | 0.5x+6=x | | 3p^2-10=-7 | | 4x^2-7x+7=5x+2 | | 2y+9=3 | | 4x^2+3x-729=0 | | x^2+4x-7=-3x+1 | | x^2+13x+37=1 | | 3(x-5)-20=8x-10 | | 8y+4=4 | | 6(9-b)=-1 | | lnx=3.19 | | 5+ln(x+2)=4 | | ln(x)=3.19 | | -0.2(34.3+3x)=0.1x | | 7c-(-8)-2c=17 | | (5x-1)2=22 | | -5x-4.2=121 |